New Programming Modes of Spinal Cord Stimulation for Chronic Pain: A Systematic Review of Outcomes with Burst and High-Frequency Technology - Bergman, Jeffrey J.; Dupré, Derrick A.; Tomycz, Nestor D. (Indian Journal of Neurosurgery, 2018)
Spinal cord stimulation (SCS) is a well-established, evidence-based treatment for chronic pain. For decades, implantation of tonic SCS systems has relied on epidural electric lead placement to overlap regions of pain with paresthesias to achieve maximal postoperative pain relief. During the course of tonic SCS treatment, tolerances to the stimulation frequency may develop, leading to reduced efficacy. Recent developments in novel programming modes, such as high-frequency 10 kHz (HF10) and burst, stray from tonic SCS in their electrical stimulation delivery patterns and unique ability to deliver SCS without engendering paresthesias. To date, no review has analyzed outcomes of both HF10 SCS and burst SCS for chronic back and limb pain. This article aims to review all HF10 and burst SCS prospective observational and randomized controlled trials for chronic back and limb pain. The literature search identified 21 papers—10 HF10 SCS papers, 9 burst SCS papers, and 2 papers assessing both HF10 and burst SCS concurrently. Burst SCS and HF10 SCS have been subjected to randomized controlled studies and have used similar patient pain score reporting on a visual analog scale (VAS) and numeric rating scale (NRS). Results from these studies have reported significant reductions in axial back pain and limb pain in patients sustained for up 20 months with burst SCS treatment and up to 36 months with HF10 SCS. Both novel programming modes show promise as viable treatments for those suffering from chronic pain and/or patients who may no longer be responders to tonic SCS.
Keywords: spinal cord stimulation; chronic pain; neurostimulation